Recent advances in functional magnetic resonance imaging: Contribution to pediatric epilepsy - Noulhiane, Marion; Pinabiaux, Charlotte; Jambaqué, Isabelle; Chiron, Catherine; Hertz-Pannier, Lucie (Journal of Pediatric Epilepsy, 2013)
New non-invasive functional magnetic resonance imaging (fMRI) techniques are deeply changing the exploration of epileptic and functional networks in childhood epilepsies, as well as of the normally developing brain. In this review, we first briefly describe the fMRI methods and the specificity, advantages and limitations of fMRI protocols and studies in pediatric epilepsies. Current fMRI applications in pediatric epilepsies mostly refer to presurgical mapping that can be performed with motor, language or memory tasks, and allows to select patients, tailor resection and sometimes predict postoperative cognitive outcome. Functional connectivity studies are currently emerging from resting state fMRI acquisitions to assess the possible consequences of epileptic activity on the development of functional long distance networks. Future directions for research applications, especially connectivity analysis, and new developments such as electroencephalography-fMRI, will lead to better comprehensive descriptions of functional brain networks in pediatric epilepsy.
Keywords: Functional magnetic resonance imaging; pediatric epilepsy; cognitive networks; resting state